(Re) thinking urban mental health from the periphery of São Paulo in times of the COVID-19 pandemic. (2nd January 2022) - Abarca Brown, Cristobal; Szabzon, Felipe; Bruhn, Lenora; Ravelli Cabrini, Daniela; Miranda, Elisangela; Gnoatto, Jacqueline; de Vries Albertin, Paula; Santana, Geilson Lima; Andrade, Laura Helena
Abstract: Urban mental health studies traditionally search for causal relationships between elements of the city and the prevalence of mental disorders. This paper discusses the importance of (re)thinking the 'lived urban experience' from the perspective of city residents about how the immediate environment affects their mental health and how people cope with inequalities. A participatory-action research was implemented in a peripheral area of São Paulo – Brazil, in which volunteers from the territory made phone calls to neighbours to provide emotional support during the COVID-19 pandemic. Weekly supervision meetings were held between volunteers and researchers to discuss the experiences shared by community counterparts. Narratives have shown that the lived experience in the city is mediated by multiple layers of 'urban insecurities'. These difficulties pressured people to organise and resist in face of pervasive inequalities as well as to respond to unfolding experiences of social suffering. We highlight the potential of participatory methodologies to observe the ways in which subjects face their structural issues and the suffering that emerge in these circumstances. The understanding of how these conflicts are lived at a subjective level can support studies that are wondering about the mechanisms of how social conflicts 'get under the skin'.